Voltammetric Analysis of Pb2+ Ion on Gold Nanoparticles-Modified ZnO Electrode - Fauziah, Rahmi; Kurniawan, Cepi (Universitas Negeri Semarang, 2021)
Waste such as heavy metal is a very dangerous toxic material, the heavy metal that is often used is lead (Pb). In this study, heavy metal detection was carried out with the material used, namely ZnO because it has high sensitivity in heavy metal detection. ZnO will be modified with gold nanoparticles (AuNP). AuNP has been used for surface decoration of oxides to obtain high sensor performance which is 6.5 times faster than without the addition of Au. Research has been carried out on the Voltammetric Analysis of Pb2+ Ion on Gold Nanoparticles-Modified ZnO Electrode. This study aims to determine the nature and characteristics of the ZnO/AuNP compound deposited on the SPCE electrode and to determine the selectivity and sensitivity of the ZnO/AuNP electrodeposition on the SPCE electrode to identify heavy metals. FTIR characterization showed that there was a Zn-O bond in the synthesized compound. SEM characterization showed hexagonal morphology. The PSA results showed the size of the AuNP was 115.7 nm. The test results of the ZnO/AuNP5%/SPCE electrode sensor have a LoD value of 2.88 ppm and a LoQ of 9.60 ppm, a sensitivity of 0.077 µA µg-1 L., and R2 = 0.96862.